Photography 101 : exposure basics, camera settings, lens info, composition tips, and shooting scenarios. (Pocket guide (Rocky Nook), 2023)
Designed for photographers who haven’t fully conquered their camera or the photographic fundamentals of exposure and composition, this handy and ultra-portable quick reference Pocket Guide helps you get the shot when you’re out and about.